Multi-User Secure Receiving Algorithm Based on Blind Recovery in MIMO Network - Yongli An; Chengming Zhang; Zhanlin Ji; Zhichao Zhou (IEEE Access, 2021)
In order to optimize the performance of data transmission in multiple input multiple output (MIMO) wireless communication systems, a spread spectrum self-interference system based on channel inverse matrix modulation is proposed. First of all, we improved the spread spectrum method and proposed the DIMMSS(channel inverse matrix modulation spread spectrum) spread spectrum method based on the channel inverse matrix. And a simulation comparison experiment was carried out for the anti-interference ability and anti-eavesdropping ability of this method. Secondly, this paper also proposes two blind despreading methods based on Walsh-hadamard algorithm and cluzeau algorithm. We studied the anti-jamming performance of these two algorithms, and optimized the blind despreading process according to their different characteristics of computational complexity. Experimental results show that compared with ordinary direct sequence spread spectrum, the spread spectrum self-interference system can not only improve the confidentiality and security of the transmitted signal, but also greatly simplify the receiving equipment. It has certain application value in the military and civilian fields.